Dyeing of Cotton Knit Fabric with Natural Dyes Extracted from Java Plum. Issue 6 (November 2021) - Uddin, Md. Koushic; Rahman, Mustafizur; Bhattacharjee, Shuva; Singh, Susmita; Mojlish, Shanjid Khan
Natural dyes extracted from natural sources are likely to be less harmful and more eco-friendly than synthetic dyes. In this study, cotton fabric was dyed with natural dyes extracted from Java plum fruit ( Syzygium cumini ). Dyeing was accomplished with or without mordanting agents using simultaneous and post-mordanting methods. The color of the treated substrates was investigated in terms K/S and CIELAB values. In addition, the attenuation co-efficient and solubility in organic solvents of the extracted dyes were determined. The wash and rubbing fastness of the dyed fabrics were good to excellent. Deep shades were obtained by post mordanting method with ferrous sulfate, whereas alum treated fabrics produced brighter shades with excellent fastness. Java plum fruit is available in many countries and offers a possible substitute for synthetic dyes.